The Impact of Mean Arterial Pressure on Functional Outcome Post Trauma-Related Acute Spinal Cord Injury: A Scoping Systematic Review of the Human Literature. (January 2018) - Sabit, Behzad; Zeiler, Frederick Adam; Berrington, Neil
Purpose: To perform a scoping systematic review on the literature surrounding mean arterial pressure (MAP) and functional outcomes post traumatic acute spinal cord injury (ASCI). Methods: We performed a systematic review of the literature via searching MEDLINE, BIOSIS, EMBASE, Global Health, SCOPUS, and Cochrane Library from inception to January 2015. We also performed a handsearch of various published meeting proceedings. Through a 2-step review process, employing 2 independent reviewers, we selected articles for the final review based on predefined inclusion/exclusion criteria. Results: Nine studies were included in the final review. Only 2 were prospective studies. All studies documented some degree of objective functional outcome in relation to MAP posttraumatic ASCI. Four studies documented a relation between higher MAP and improved functional outcome. Five studies failed to show any relationship between MAP and functional outcome. Conclusions: Although no definitive conclusions could be reached based on the data collected, this study does give valuable insight into future avenues of research on the topic of hemodynamic management in traumatic ASCI as well as provides guidelines for refinement of future study design.